2002
DOI: 10.1016/s1010-7940(01)01108-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of operative mortality following primary coronary artery bypass surgery

Abstract: Our data suggest that prior to operation, operative mortality can be best predicted by urgency of operation and left ventricle ejection fraction. After performing the operation, prognostic factors include preoperative LVEF < or = 35%, non-elective operation, and prolonged cardiopulmonary bypass time. Further study is required to assess the generalization of our findings to Iranian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
2
18
0
2
Order By: Relevance
“…During the time period of our study increasingly older patients with more comorbidities were referred for CABG in accordance with findings in other reports [14][15][16]. Despite documented increase of patients' risk factors over time others and we have observed a progressively declining hospital mortality [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…During the time period of our study increasingly older patients with more comorbidities were referred for CABG in accordance with findings in other reports [14][15][16]. Despite documented increase of patients' risk factors over time others and we have observed a progressively declining hospital mortality [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…1,19 The absence of such variables as age and sex may seem surprising, but these fi ndings are echoed by other studies. 1,19,20 It is noteworthy that Ivanov et al reported a remarkable decline in the operative mortality of elderly patients despite an increase in the prevalence and severity of their risk profi le. 20 Other studies in agreement or disagreement with our results are listed in Tables 4 and 5.…”
Section: Discussionmentioning
confidence: 91%
“…Tremendous efforts have been made to develop risk stratifi cation models for a more accurate risk prediction of the mortality of patients undergoing CABG, [1][2][3] which is now the most commonly performed major operation in the world. However, these risk models must be applied with caution and only after careful study and calibration for any specifi c population.…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have reported that LCOS is a rare event after cardiac surgery using cardiopulmonary bypass with incidence rates reaching 0.1 to 2% [11,12], these numbers may be considerably higher in patients undergoing CABG surgery. Regarding the Brazilian data about LCOS after CABG, few studies have been published.…”
Section: Discussionmentioning
confidence: 93%